2016
DOI: 10.1038/srep27753
|View full text |Cite
|
Sign up to set email alerts
|

Cbx7 is epigenetically silenced in glioblastoma and inhibits cell migration by targeting YAP/TAZ-dependent transcription

Abstract: Glioblastomas (GBM) are the most malignant form of astrocytomas which are difficult to treat and portend a grave clinical course and poor prognosis. In this study, we identified Chromobox homolog 7 (Cbx7), a member of Polycomb Repressive Complex 1 (PRC1), as a downregulated gene in GBM owing to its promoter hypermethylation. Bisulphite sequencing and methylation inhibitor treatment established the hypermethylation of Cbx7 in GBM. Exogenous overexpression of Cbx7 induced cell death, inhibited cell proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Bioinformatics analysis revealed 1,046 (442 genes upregulated and 604 genes downregulated) and 1,109 (447 genes upregulated and 662 genes downregulated) differentially expressed genes upon PTC-209 treatment respectively in U87MG and T98G cells (fold change > 2) ( Figure 5(b) and Supplemental Table S3 and S4). Interestingly, several suppressors of glioblastoma growth, invasion or stemness are significantly upregulated, such as CBX7 [21,23], TIMP4 [24], SFRP2 [25], KLF9 [26], as validated by qRT-PCR analysis in U87MG cells ( Figure 5(c)). Probably due to different genetic background, the KEGG analyses of the derepressed genes in U87MG and T98G cells revealed distinct enrichment of pathways (Supplementary Figure S3A and B).…”
Section: Ptc-209 Reverses the Altered Transcriptional Program Associamentioning
confidence: 74%
See 1 more Smart Citation
“…Bioinformatics analysis revealed 1,046 (442 genes upregulated and 604 genes downregulated) and 1,109 (447 genes upregulated and 662 genes downregulated) differentially expressed genes upon PTC-209 treatment respectively in U87MG and T98G cells (fold change > 2) ( Figure 5(b) and Supplemental Table S3 and S4). Interestingly, several suppressors of glioblastoma growth, invasion or stemness are significantly upregulated, such as CBX7 [21,23], TIMP4 [24], SFRP2 [25], KLF9 [26], as validated by qRT-PCR analysis in U87MG cells ( Figure 5(c)). Probably due to different genetic background, the KEGG analyses of the derepressed genes in U87MG and T98G cells revealed distinct enrichment of pathways (Supplementary Figure S3A and B).…”
Section: Ptc-209 Reverses the Altered Transcriptional Program Associamentioning
confidence: 74%
“…However immunohistochemical (IHC) stainings have shown that BMI-1 is highly expressed in GBM samples [11]. Hence the expression of BMI-1 is likely to be regulated through posttranscriptional mechanisms as previously suggested [23,24].…”
Section: Bmi-1 Is Highly Expressed In Glioblastoma Cell Lines and Primentioning
confidence: 90%
“…Recent studies have implicated TEADs as master regulators of cell invasion in melanoma 42 . Few studies have also begun to investigate YAP-TEAD activity in GBM malignancy 38 , 62 68 . Specifically, disruption of TEAD2/4 binding to TAZ or shRNA-mediated knockdown of TAZ has been shown to result in deficient GBM cell migration 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Our GSEA analysis also indicated a "normal like", more differentiated phenotype of low PPS20 tumors with an enrichment of digestion and ion channel transport related gene sets. Among genes upregulated in this group, CBX7, MIA3 and KANK1 have been shown to have tumor suppressive activities including roles in inhibition of PLOS ONE cellular motility/migration and/or proliferation, and induction of cell cycle arrest in various malignancies [60][61][62][63][64][65][66][67]. PITPNA which we found as a good prognostic indicator, is suggested as favorable prognostic marker in pancreatic, endometrial and renal cancers in the Human Protein Atlas (www.proteinatlas.org) [68], and its overexpression was associated with longer survival in PDAC [69].…”
Section: Plos Onementioning
confidence: 99%